Rediscovery of Pseudomyrmecion ramalium Bedel, 1885: a rare endemic saproxylic Longhorn beetle in the Djebel Edough Forest, Algeria (Coleoptera, Cerambycidae) - Hadiby, Rached; Boukheroufa, Mehdi; Vitali, Francesco; Adjami, Yasmine; Frih, Abdelaziz; Sakraoui, Feriel (Zootaxa, 2025)
The rediscovery of Pseudomyrmecion ramalium Bedel, 1885, a rare and endemic saproxylic longhorn beetle, in the Djebel Edough forest in Algeria is reported. Hind wings are for the first time showed and described, evidencing the brachyptery of this species. Erroneous nomenclatorial, biological and chorological data referred by previous authors are discussed and corrected. This species, which had not been observed in the region since 1900, is an obligate saproxylic insect exclusively associated with the Algerian oak Quercus canariensis Willd. Classified as an endangered species on the IUCN Red List due to its rarity and the threats to its habitat, P. ramalium represents a conservation priority. Its rediscovery highlights the need for further research to assess the current state of its population and better understand its ecological requirements. This information will be crucial for developing effective conservation strategies and preserving its fragile habitat.